Let x be the unknown positive real number. Then, we can write our statement mathematically as
![x^2=11x+42](https://img.qammunity.org/2023/formulas/mathematics/college/f5ilzcc23dr0vodisscobiq10xhzrun3xd.png)
then, by moving the right hand side, we have
![x^2-11x-42=0](https://img.qammunity.org/2023/formulas/mathematics/college/2n4by459s1gbkn5ncko0rvl6m08dzbija8.png)
and we can solve this equation by means of the quadratic formula
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
where, in our case, a=1 (the coefficient of x squared), b =-11 and c=-42. By substituting these values into the last formula, we get
![\begin{gathered} x=\frac{-(-11)\pm\sqrt[]{(-11)^2-4(1)(-42)}}{2(1)} \\ x=\frac{11\pm\sqrt[]{121+168}}{2} \\ x=\frac{11\pm\sqrt[]{289}}{2} \\ x=(11\pm17)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/87b5sd6kwo9sdenlquvnonhtex3d2q39hv.png)
the first solution is given by taking the + sign and the secon solution with the - sign. Then, we have
![\begin{gathered} \text{First solution: } \\ x=(11+17)/(2)=(28)/(2)=14 \\ \text{Second solution} \\ x=(11-17)/(2)=-(6)/(2)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h6cu7jo091xkav2gzlp85kbbx8413la1u9.png)
However, we need the positive real number. Then, the solution must be x=14.